Gradasi Potensial Material Daur Ulang Pasca Bencana Kota Palu sebagai Bahan Penyusun Perkerasan Lentur - Novita Pradani; Rita Irmawaty; Muhammad Wihardi Tjaronge; Irwan Ridwan Rahim (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2022)
The earthquake in Central Sulawesi in September 2018, accompanied by tsunami and liquefaction, caused very significant infrastructure damage, especially in Palu City. Roads are one of the vital infrastructures that have suffered a lot of damage. Efforts to rehabilitate roads due to the disaster have been carried out and have left quite a lot of old road pavement material. This dredging material needs to be optimized for use, especially in new pavements. Because this can make new materials efficient, especially aggregates in the pavement mixture. The use of new aggregates can be conditioned to a minimum by making efficient use of recycled materials. Namely by determining the type of pavement layer that best suits the gradation conditions of the recycled material. The purpose of this study was to obtain the type of flexible pavement layer that best suits the gradation of post-disaster recycled material based on standard specifications. The method used is sieving analysis of recycled material from several locations in Palu City that were affected by the disaster. The results showed that the use of post-disaster recycled materials, based on the recycled aggregate suitability value, was the AC-WC layer of 78.33%, the HRS-WC layer of 70%, the AC-BC layer of 66.67%, the layer of AC-Base is 41.67% and SMA-Thin layer is 40%. Based on the grading analysis, post-disaster recycled material in Palu City is most suitable for the AC-WC layer type because the addition of new aggregate is the least, resulting in the most optimal use of recycled material.Kata kunci: Recycled Material, Post Disaster Material, Flexible Pavement, Gradation